Postpartum Depression and Diabetes - Pawan Sharma; Sanjay Kalra; Yatan Pal Singh Balhara (Journal of the Pakistan Medical Association, 2022)
Depression and diabetes share a bidirectional causal association. Additionally, during the postpartum period women have an increased vulnerability for both depression and impaired glucose tolerance. The impact of the comorbidity of diabetes and postpartum depression is also bidirectional with an impaired course and outcome of both these disorders. The clinic visits for pregnancy and/ or diabetes care offer important opportunity to screen for postpartum (as well as prepartum) depression. Screening tools that are shorter, that take less time and acceptable are recommended. While a limited number of guidelines on management of depression among persons with diabeteshave commented on management of the postpartum depression, the emphasis is on timely intervention using pharmacological and psycho- social interventions. Continue...